Nursing transfer of accountability at the bedside: partnering with patients to pilot a new initiative in Ontario community hospitals - Kristina Miller; Aden Hamza; Kateryna Metersky; Dianne Gaffney (The Beryl Institute, 2018)
The transfer of accountability (TOA) for a patient from one nurse to another at change of shift is an important opportunity to exchange essential patient care information, as well as to enhance the safety and quality of patient care. This study was undertaken to explore nurses', patients' and family members' perceptions associated with the implementation of bedside nurse to nurse TOA. Focus groups were conducted pre-implementation (two with nurses and two with patients and family members) and post-implementation (six with nurses and two with patients and family members). The focus groups were audio-recorded, transcribed and analysed using directed content analysis. Findings were divided into positive outcomes and challenges to bedside nurse to nurse TOA. Positive outcomes included increased patient safety, more informed patients more consistent use of whiteboards in the patient rooms, better engagement with family via the whiteboard and increased family involvement, confirmation of information between nurses, increased accountability between nurses, and personal introduction/icebreaker of the new nurse. The inclusion of the Patient Partners on the project team was a key success factor for the project. Challenges included a perception of lengthened time required for TOA and increased workload, lack of privacy and potential breaches of confidentiality, patient fear and lack of comprehension, lack of clarity in TOA processes, and inconsistent application of the procedures. Hospital administrators and nurse leaders can use these findings to anticipate and understand change associated with bedside TOA as seen by both nurses and patients/families.